Spectroscopic study of proteins - Klaudia Kierszniok; Patrycja Dolibog; Barbara Pietrzyk; Tomasz Pryzwan (Annales Academiae Medicae Silesiensis)
Proteins are macromolecular compounds made up of amino acids linked by peptide bonds. They are the basic structural component of all living organisms. Their diversity has to do with their structure, and therefore with the way the amino acid residues are arranged in the molecule. Albumin shape is determined by the sequence of amino acids that make it up. The primary amino acid in its composition is cysteine and in smaller amounts glycine, methionine and one tryptophan residue, thanks to which it exhibits fluorescent properties. For structural studies of proteins, many physical methods are used. The most commonly chosen are spectroscopic methods, which deal with the interaction between electromagnetic radiation and matter. The article provides an overview of spectroscopic methods employed in the structural studies of proteins. It also serves as a prelude to further research that aims to utilise one of the spectroscopic methods to study the structural changes of albumin after exposure to physicochemical agents. The described spectroscopic methods are characterized by different sensitivity, specificity and procedures to be performed during sample preparation for the study. In the spectroscopic study of proteins, with particular attention to changes in their structure, the method of fluorescence spectroscopy deserves attention. It is the best choice for studying structural changes in proteins that occur under the influence of physicochemical factors. Capturing these changes and relating them to the functions of proteins enriches the knowledge of the normal functioning of the body, as well as the basis of some diseases.